Fiscal Decentralization and Revenue Stability in the Kyrgyz Republic, 1993-2010 - Temirlan MOLDOGAZIEV (Eurasian Journal of Business and Economics, 2012)
This study examines whether the policies of fiscal decentralization in the Kyrgyz Republic (1993-2010) had any effect on revenue stability at the national level. We find reasonable evidence of revenue volatility at the national level due to instabilities in subnational revenues. In terms of tax buoyancy measures, the revenues at the national level have to grow faster to compensate for the decreasing size of revenues at the subnational level. As to the measures of tax elasticity, we find that the income tax base, and VAT to a lesser extent, grew much less rapidly than the indicator for economic activity. As a result, revenue adequacy has suffered in the Kyrgyz Republic both at national and subnational levels.